Identification of volatile organic compounds (vocs) as biomarkers of potato rots during cold storage and ecophysiological study of the pathogens involved. - Gutiérrez-Pozo, Maria (Cranfield University, 2021)
Potato tubers are stored for up to ten months. Therefore, controlling the conditions (temperature and relative humidity) in the storage environment is essential to reduce the risk of appearance of potato diseases. Fluctuations in the environmental conditions appear throughout the storage room, allowing the development of potato rots. This work aimed to identify Volatile Organic Compound (VOC) biomarkers of potato diseases to achieve an early identification of potato rots under commercial storage conditions. Furthermore, to achieve a deep understanding of the ecophysiology of the fungal and bacterial pathogens involved. Some of the objectives of this study were the isolation of fungal pathogens from potato tubers, the study of the mycotoxin production in the presence of dry rot, the development of a methodology for the VOC sampling and identification, and the study of the effect of storage time on the potato susceptibility to dry rot and soft rot. A method for the untargeted detection and identification of VOCs produced by potatoes during storage was developed using Thermal Desorption-Gas Chromatography-Time of Flight- Mass Spectrometry. A range of different TD (Thermal desorption) tubes were evaluated, and the most suitable for the adsorption of VOCs under the study conditions were selected. An in vitro study of the pathogens responsible for gangrene and dry rot was carried out using Natural Potato Dextrose Agar (PDA) and three different temperatures (5,10 and 15ᴼC) and water activities (aw) (0.97, 0.98, 0.99). Higher temperature and aw resulted in higher growth rate and lag time of both pathogens, Fusarium spp. and Boeremia foveata. Furthermore, mycotoxins, such as T-2, HT- 2, diacetoxyscirpenol, beauvericin and neosolaniol, were detected in potato tubers infected with dry rot. An in vivo study of dry rot and soft rot was carried out at 8.5ᴼC, using two cultivars with different susceptibility to these diseases (cvs. Record and Casablanca). The internal and external lesions resulting from the infection were assessed over time and the VOC fingerprint of each cultivar at each time point was determined. The effect of storage time on the disease severity was also evaluated, demonstrating that at 8.5ᴼC, only dry rot’s severity was affected by the longer storage time, while no effect was observed in soft rot. Several VOCs were detected in higher abundance in presence of the pathogen in the in vivo and in vitro studies. They were selected as potential biomarkers of dry rot, soft rot and gangrene. Ethanol, acetone, ethyl acetate and acetic acid were detected in vitro as potential indicators of the presence of a fungal or bacterial disease. Furthermore, 2-methylpropan-1-ol was selected as a potential indicator of the presence of a fungal pathogen, such as Fusarium spp., responsible for dry rot in potato tubers. In vivo, 1-methoxy-3-methylbutane, 2- butanone, dimethyl disulfide and hydrogen cyanide were detected as potential biomarkers of dry rot or soft rot in potato tubers. Lastly, based on the findings that have been achieved in this work, future research should be focused on the study of the growth and VOC production of Pectobacterium carotovorum spp. in vitro and the study of the disease severity and VOC production of gangrene in vivo. Furthermore, a validation of the VOC results achieved in this work under commercial storage conditions should be carried out. These studies will confirm and enhance the findings achieved in this work.
Keywords: gangrene; dry rot; soft rot; TD-GC-ToF-MS; Fusarium sambucinum; Pectobacterium carotovorum atrosepticum; Fusarium oxysporum; Boeremia foveata; potato storage; mycotoxins; disease severity